Swedish - Finnish glossary: administrative words - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Swedish - Finnish glossary with administrative words. Contains 110 entries. 2011.

Swedish - Finnish glossary with administrative words. Contains 110 words. 2011.

En svensk-sverigefinsk ordlista med förvaltningsord. Innehåller 110 uppslagsord. 2011.
Svensk-finsk ordlista: förvaltningsord
Keywords: administration; administration; administrative law; förvaltningsrätt; management; förvaltning; administration; administration, förvaltning; Administrative units; Administrativa enheter; word list; ordlista; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur